Total synthesis and dual PPAR alpha/gamma agonist effects of Amorphastilbol and its synthetic derivatives - Kim, Taejung; Lee, Woojung; Jeong, Kyu Hyuk; Song, Jung Ho; Park, Soon-Hye; Choi, Pilju; Kim, Su-Nam; Lee, Seokjoon; Ham, Jungyeob (Pergamon Press Ltd., 2012)
Amorphastilbol (APH-1), isolated from a Robinia pseudoacacia var. umbraculifer seed extract, is a biologically interesting natural trans-stilbene compound with dual peroxisome proliferator-activated receptor (PPAR) alpha/gamma agonist activity. After total synthesis of APH-1 and its derivatives by Pd-catalyzed Suzuki-Miyaura cross-coupling of a common (E)-styryl bromide intermediate and various aromatic trifluoroborate compounds, we biologically evaluated APH-2-APH-12 for PPAR agonist activity. APH-4 and APH-11 were effective PPAR alpha/gamma transcriptional activators, compared with APH-1. Therefore, we suggest that APH-4 and APH-11 are novel dual PPAR alpha/gamma agonists and are potentially useful for treating type 2 diabetes by enhancing glucose and lipid metabolism. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: POMEGRANATE FLOWER; INSULIN-RESISTANCE; MULTIMODAL DRUGS; ACTIVATION; GAMMA; TRIGLYCERIDES; HYPERGLYCEMIA; MODULATORS; PREVENTS; EXTRACT